ANALISIS PENGARUH PROFITABILITAS, BONUS PLAN, DAN DEBT COVENANT TERHADAP TAX AVOIDANCE DENGAN TRANSFER PRICING SEBAGAI VARIABEL MEDIASI - Novianty Novianty; Vito Apriyanto (LPPM Universitas Bina Bangsa, 2024)
This research aims to examine aspects of variables that are considered related and can influence the occurrence of tax avoidance. The variables used in this research are Profitability, Bonus plan, Debt covenant, and Transfer pricing as mediation of tax avoidance motives. Data collection used a purposive sampling method which focused on raw goods sector companies listed on the IDX from 2018 to 2022. Sampling was chosen with a total of 115 data. The data analysis methods used include multiple linear analysis and the Sobel Test. The results of this research reveal that Profitability and Debt Covenant have a negative effect on Tax Avoidance, the Bonus Plan has a positive effect on Tax Avoidance, and Transfer Pricing cannot mediate the effect of Profitability, Bonus Plan and Debt Covenant on Tax Avoidance